2014
DOI: 10.1128/jvi.03515-13
|View full text |Cite
|
Sign up to set email alerts
|

Increased Stability and Limited Proliferation of CD4 + Central Memory T Cells Differentiate Nonprogressive Simian Immunodeficiency Virus (SIV) Infection of Sooty Mangabeys from Progressive SIV Infection of Rhesus Macaques

Abstract: Depletion of CD4 ؉ central memory T (TCM) cells dictates the tempo of progression to AIDS in simian immunodeficiency virus (SIV)-infected rhesus macaques (RMs IMPORTANCE Comparison of the immunologic effects of simian immunodeficiency virus (SIV) infection on rhesus macaques (RMs), a speciescharacterized by progression to AIDS, and natural host sooty mangabeys (SMs), a species which remains AIDS free, has become a useful tool for identifying mechanisms of human immunodeficiency virus (HIV) disease progression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Because the expression of Ki-67 was higher in VNPs than in PPs, while immune activation markers such as HLA-DR and CD38 were expressed at similar levels, we propose that, in VNPs, the combination of increased CD4+ T memory cell proliferation and low levels of direct virus infection of CD4+ T SCM and T CM cells may be reflective of more efficient homeostatic proliferation, a physiologic process induced by loss of lymphocytes, rather than overt activation. Indeed, in non-pathogenic infection of SMs, there is a similar association between T CM count and proliferation [40]. However, whether these factors represent a cause or consequence of lack of progression in VNPs and altered T CM and T SCM infection is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Because the expression of Ki-67 was higher in VNPs than in PPs, while immune activation markers such as HLA-DR and CD38 were expressed at similar levels, we propose that, in VNPs, the combination of increased CD4+ T memory cell proliferation and low levels of direct virus infection of CD4+ T SCM and T CM cells may be reflective of more efficient homeostatic proliferation, a physiologic process induced by loss of lymphocytes, rather than overt activation. Indeed, in non-pathogenic infection of SMs, there is a similar association between T CM count and proliferation [40]. However, whether these factors represent a cause or consequence of lack of progression in VNPs and altered T CM and T SCM infection is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…After their restoration, CD4 + central memory cells (T CM ) are lost in SIVsmm-infected SMs at rates 20 times slower than those of SIV-infected RMs (McGary et al, 2014). This translates to a half-life of total T CM populations <16 months for RMs, but >17 years for SMs, which is in agreement with the rare cases of AIDS in natural hosts in very old animals.…”
Section: Post-transmission Features That May Impact Siv Pathogenesmentioning
confidence: 99%
“…This translates to a half-life of total T CM populations <16 months for RMs, but >17 years for SMs, which is in agreement with the rare cases of AIDS in natural hosts in very old animals. Also, SM CD4 + T CM proliferation levels are lower than in RMs and the RM T CM proliferation correlates with viral replication (McGary et al, 2014). Yet, a recent study of mandrills in Gabon found a significant decrease in memory T-cells populations that was correlated with the duration of infection (Greenwood et al, 2014).…”
Section: Post-transmission Features That May Impact Siv Pathogenesmentioning
confidence: 99%
“…SIV-infected RM have high levels of viral DNA in both CD4 ϩ central memory T (TCM) cells and effector memory (TEM) cells, while infected SM have high viral DNA levels in TEM cells but much lower levels in TCM cells (8). Relative sparing of TCM cells in natural hosts may favor the preservation of CD4 ϩ T cell homeostasis (8,25). Other subsets that are differentially affected in natural and nonnatural hosts that may affect T cell homeostasis, immune competence, or other functions include CD4 ϩ T stem cell memory (TSCM) cells and T follicular helper (TFH) cells, as well as distinct localization patterns within lymphoid tissues (9,26).…”
Section: Cd4mentioning
confidence: 99%